Dimension of images of large level sets - Armstrong, Gavin; O'Farrell, Anthony G. (Mathematica Scandinavica, 2022)
Let $k$ be a natural number. We consider $k$-times continuously differentiable real-valued functions $f\colon E→ \mathbb{R} $, where $E$ is some interval on the line having positive length. For $0